Single point mutations reveal amino acid residues important for Chromobacterium violaceum transaminase activity in the production of unnatural amino acids - Fayne, Darren; Almahboub, Sarah A.; Narancic, Tanja; O'Connor, Kevin E. (My University, 2018)
Unnatural amino acids (UAAs) are chiral amines with high application potential in drug discovery and synthesis of other valuable chemicals. Biocatalysis offers the possibility to synthesise novel optically pure UAAs with different physical and chemical properties. While the biocatalytic potential of transaminases in the synthesis of UAAs has been demonstrated, there is still a need to improve the activity with non-native substrates and to understand which amino acids residues are important for activity with these UAAs. Using a rational design approach, six variants of Chromobacterium violaceum DSM30191 transaminase (CV_TA) carrying a single and one variant carrying two substitutions were generated. Among the variants with a single substitution, CV_Y168F showed a 2 to 2.6-fold increased affinity for 2-oxooctanoic acid (2-OOA) and 3-oxobutyric acid (3-OBA) methyl ester used to synthesise an α- and β-UAA. Analysis of the first half of the transaminase reaction showed no change in the activity with the donor (S)-1-phenylethylamine. The combination of W60C and Y168F substitutions improved the CV_TA affinity for 2-OOA 10-fold compared to the wild type. Other substitutions showed no change, or reduced activity with the tested substrates. Our findings provide structural information on CV_TA and demonstrate the potential of rational design for biosynthesis of UAAs
PUBLISHED
Keywords: Unnatural amino acids; Chromobacterium violaceum; Aminod acids